Analyzing Teacher’s Perception of Teacher-Students Interaction Based on Gender Perspective - Yuliana Dg. Macora; Nur Elsa Lahawua (Sintuwu Maroso Journal of English Teaching, 2020)
This research aims to determine the teacher’s perception of teacher-student interaction in the classroom. This research is conducted in SMA Negeri 3 Poso. The method used in this research is descriptive qualitative. The subject is the English teacher and the students of tenth grade. The data are collected by observation about teacher-student interaction in the classroom and interviews with English teachers and somestudents of Academic Year 2017/2018. The result of the research shows that all students receive equal attention or help from the teacher, all students receive praise verbal is equal. While male students more participative in the classroom and they also usually get verbal sunction from the teacher